Det umuliges kunst - Haarder, Andreas (Grundtvig-Studier, 1985)
The Art of the Impossible A Grundtvig Anthology. Selections from the writings of N. F. S. Grundtvig. Translated by Edward Broadbridge and Niels Lyhne Jensen. General Editor: Niels Lyhne Jensen. James Clarke, Cambridge & Centrum, Viby 1984. Reviewed by Professor Andreas Haarder, Odense University How can Grundtvig ever be translated? Professor Haarder considers it well-nigh impossible, which does not mean, however, that the attempt is not worth making. But he has some criticism of various things which need correcting for a later edition. In particular the translation of the words folkeh.jskole and Norden and the use of different terms for the same concept. He would prefer “folk high school” and “the North”, “Nordic” or “Norse”, and he thinks that the word “Scandinavia” should be avoided. The reason is that it is difficult to understand what a folk high school actually is, and that the Nordic past for Grundtvig included the English. The term “folk high school” is used elsewhere, for example in the Danish Institute’s book on Grundtvig. Professor Haarder praises the idea and the planning of the book, but he also notes too many printing errors and deficiencies in the notes. In Haarder’s opinion the most successful translations are of the sermons and the simplest songs. The selection from Norse Mythology reads well in English, which surprises him somewhat because of Grundtvig’s very intricate style. Some of that inspiration is missing from The School for Life, in both the original and the translation, but the text is pioneer work and worth including. As “a particular type of prose” he finds the extracts from Elementary Christian Teachings also readable in English. With regard to the poetry, he agrees with the editor that “It has not been Grundtvig’s good fortune to find a translator who combines a grasp of his vision with a gift of imagery matching his.” Andreas Haarder ends with a word of thanks for the step that has been taken with this anthology of Grundtvig in English.